Linking Distributed and Integrated Fiber‐Optic Sensing. Issue 16 (26th August 2022) - Bowden, Daniel C.; Fichtner, Andreas; Nikas, Thomas; Bogris, Adonis; Simos, Christos; Smolinski, Krystyna; Koroni, Maria; Lentas, Konstantinos; Simos, Iraklis; Melis, Nikolaos S.
Abstract: Distributed Acoustic Sensing (DAS) has become a popular method of observing seismic wavefields: backscattered pulses of light reveal strains or strain rates at any location along a fiber‐optic cable. In contrast, a few newer systems transmit light through a cable and collect integrated phase delays over the entire cable, such as the Microwave Frequency Fiber Interferometer (MFFI). These integrated systems can be deployed over significantly longer distances, may be used in conjunction with live telecommunications, and can be significantly cheaper. However, they provide only a single time series representing strain over the entire length of the fiber. This work discusses theoretically how a distributed and integrated system can be quantitatively compared, and we note that the sensitivity depends strongly on points of curvature. Importantly, this work presents the first results of a quantitative, head‐to‐head comparison of a DAS and the integrated MFFI system using pre‐existing telecommunications fibers in Athens, Greece. Plain Language Summary: New technologies are being developed to measure earthquakes using fiber‐optic telecommunications cables. The most popular new method in recent years is "Distributed Acoustic Sensing, " (DAS) in which pulses of light are repeatedly sent down a fiber and one measures the signals that reflect back. Shaking from an earthquake will stretch the fiber and the signature of reflected pulses will change. A new method (Microwave Frequency Fiber Interferometer [MFFI] in the paper) sends light from one end to the other and measures differences in optical phase. The new method has many advantages: it is cheaper, can be used on longer cables, and can be used at the same time as active telecommunications. As a disadvantage is lacks the high spatial resolution that DAS offers. This paper discusses the differences between the two methods and shows how to compare them, and then shows the first real‐data, head‐to‐head comparison from an earthquake observed in Athens, Greece. Key Points: We develop and test a theory for the quantitative comparison of distributed and integrated fiber‐optic strain sensing The sensitivity of integrated measurements depends primarily on local fiber curvature and fiber heterogeneity A data‐based comparison corroborates the theory, thereby demonstrating the geophysical value of our integrated sensor system